Improving the process of higher paraffin dehydrogenation on the basis of nonstationary kinetic model; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 2 - Ivashkina H. N.; Yuriev Е .М.; Kravtsov A. V. Anatoly Vasilyevich; Ivanchina E. D. Emilia Dmitrievna (Chemistry, 2007)
Заглавие с титульного листа